Magnetism and Microstructure Characterization of Phase Transitions in a Steel - M. Güler (Advances in Condensed Matter Physics)
We present phase transitions in a low carbon steel according to existing phases and their magnetism. Scanning electron microscope employed research to clarify and evaluate the microstructural details. Additionally, we utilized from Mössbauer spectroscopy for magnetic characteristics of different existed phases. Scanning electron microscope examinations showed that the pure state of the steel was fully in the ferrite phase with equiaxed grains. Moreover, subsequent heat treatments on the studied steel also ensured the first austenite and then pearlite phase formation. Mössbauer spectroscopy of these phases appeared as a paramagnetic single-line absorption peak for the austenite phase and ferromagnetic six-line spectra for both ferrite and pearlite phases. From Mössbauer data, we determined that the internal magnetic fields of ferrite and pearlite phases were as 32.2 Tesla and 31.3 Tesla, respectively.